Aplikasi Ekstraks Pewarna Alami Bunga Morning Glory (Ipomoea Purpurea) pada Preparat Section - Sri Wahyuni; Siti Zaenab; Windi Kurniasari; Ayu Iriani; Dewinta Hapsari Maharani (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Preparing requires colouring to clarify or sharpen various tissue parts, especially cells. The use of synthetic dyes in preparations in the long term can less impact both living things and the environment. The study aims to obtain natural dyes from morning glory flowers at optimal temperatures and pH and find out the feasibility of preparations coloured using Morning Glory flower extract. Method: The extraction process uses a maceration method with different temperature variations of 400C, 500C, 600C, 700C, 800C and different pH i.e. 3, 4, 5, 6. The preparation process uses different dye concentration variations. The concentrations used are 50%, 60%, 70%, 80%, 90%, 100%. Data analysis techniques use descriptive and percentage analysis methods. Results: Morning glory flower extract (Ipomoea purpurea (L.) Roth) can colour dermal tissue, empulur, cortex and transport beams on the stems of cayenne pepper plants (Capsicum frutescens L.). Conclusion: Natural dyes of morning glory flowers can be used as a learning medium with a 74% eligibility rate for preparing with morning glory flower dyes.